Giant elastocaloric effect in directionally solidified Ni–Mn–In magnetic shape memory alloy. (August 2015) - Huang, Y.J.; Hu, Q.D.; Bruno, N.M.; Chen, Jing-Han; Karaman, I.; Ross, Joseph H.; Li, J.G.
Abstract : We have studied the giant elastocaloric effect of directionally solidified Ni–Mn–In magnetic shape memory alloys (MSMAs) near room temperature. The textured microstructure significantly enhances the ductility of Ni–Mn-based MSMAs, which allows obtaining the martensitic transition characteristics of polycrystalline samples in a uniaxial stress field. A significant cooling level of about 4 K is measured when the stress is released. The experimentally measured temperature changes are found to be in good agreement with the theoretically calculated values.